Terms from Public Agencies - Dahlberg, Simon; Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Terminological resources collected from Swedish public agencies

Terminologiska resurser inhämtade från svenska myndigheter
Termer från myndigheter
Keywords: PUBLIC ADMINISTRATION; OFFENTLIG FÖRVALTNING; Social Sciences; Samhällsvetenskap; Languages and Literature; Språk och litteratur; Public Administration Studies; Studier av offentlig förvaltning